The Role of the Rembitan Ancient Mosque in the Pemole Procession in Rembitan Village - Lalu Iman Novian Wahyudi; Antariksa Antariksa; Johanes Parlindungan (Green Publisher Indonesia, 2022)
The Rembitan village is one of the villages in Pujut Subdistrict that still maintains the traditional traditions and culture of the Sasak Tribe. This tradition has built a system of life for the Sasak people who are believed to bring good for themselves and the group. This tribe is a good community and that has been oriented to Ancient Mosque Rembitan which builds the existing traditions and culture. At this time the tradition of this tradition began to decrease in demand and the understanding of its successors related to polishing culture began to decrease due to cultural acculturation. For this reason, there needs to be a continuity of cultural knowledge for the next generation to ensure the preservation of the culture and uniqueness of the region. The purpose of this research is to describe the value contained in polishing culture so that the next generation can learn and understand the meaning and purpose of each tradition carried out by its predecessors. This study shows that the role of the Ancient Mosque of Rembitan is very visible and orientates every activity in Rembitan Village. This is manifested in the form of beliefs, attitudes, and visible symbols such as settlements and indigenous polishing activities. The results of the analysis showed that the role of the Ancient Rembitan mosque was as a space or container for the people of Rembitan Village in carrying out every process of life, both in the form of physical and cultural activities (polishing).